Severe clinical conditions associated with Bacillus cereus and the apparent involvement of exotoxins. Issue 3 (March 1979) - Turnbull, P C; Jørgensen, K; Kramer, J M; Gilbert, R J; Parry, J M
Abstract : Twenty-one cases of infection with Bacillus cereus are summarised. The histories supplied showed that at least 15 of these were associated with severe or potentially severe symptoms including two deaths. Analysis of the production of exotoxins, including haemolysin and phospholipase, by these strains is given, and the relevance of these metabolites to the severity of the condition is discussed. Three incidents of bovine mastitis resulting from B. cereus and involving three deaths are also included. The observations presented here together with those of previous reports which are reviewed indicate that B. cereus may be of clinical importance, not just an opportunist but also as an agent of potentially severe infections in its own right.